Transforming healthcare with qualitative research - Rapport, Frances, 1960-; Braithwaite, Jeffrey, 1954- (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Drawing on the knowledge and experiences of world-renowned scientists and healthcare professionals, this important book brings together academic, medical and health systems accounts of the impact of applying qualitative research methods to transform healthcare behaviours, systems and services"--
Part 1. Ideas -- Chapter 1. Introduction: Why this book? / Frances Rapport and Jeffrey Braithwaite -- Chapter 2. Qualitative Evidence Synthesis and Conceptual Development / Nicky Britten -- Chapter 3. The Life-Project of Personal Wellbeing: Modern healthcare and the individuality of health / Nigel Rapport -- Chapter 4. Socio-Narratology and the Clinical Encounter Between Human Beings / Arthur W Frank -- Chapter 5. Interrupted Body Projects and the Narrative Reconstruction of Self / Andrew C Sparkes -- Chapter 6. The Fourth Research Paradigm: Activating researchers for real world need / Frances Rapport and Jeffrey Braithwaite -- Part 2. Systems -- Chapter 7. Slack Resources in Healthcare Systems: Waste or resilience? / Tarcisio Abreu Saurin and Dayane MC Ferreira -- Chapter 8. Using Qualitative Methods to Understand Resilience in Complex Systems / Zeyad Mahmoud, Kate Churruca, Louise A Ellis, Robyn Clay-Williams and Jeffrey Braithwaite -- Chapter 9. Qualitative Assessment to Improve Everyday Activities: Work-as-imagined and work-as-done / Robyn Clay-Williams, Elizabeth Austin, Jeffrey Braithwaite and Erik Hollnagel -- Chapter 10. Narrativizing Cancer Patients' Longitudinal Experiences of Care: Qualitative inquiry into lived and online melanoma stories / Klay Lamprell, Frances Rapport and Jeffrey Braithwaite -- Chapter 11. Look the Other Way: Patient-centred care begins with care for our physicians / Klay Lamprell, Frances Rapport and Jeffrey Braithwaite -- Chapter 12. Resilient Healthcare in Refractory Epilepsy: Illuminating successful people-centred care / Patti Shih, Frances Rapport, Janet C Long, Emilie Francis-Auton, Mia Bierbaum, Mona Faris and Robyn Clay-Williams -- Part 3. Solutions -- Chapter 13. Sensemaking as a Strategy for Managing Uncertainty: Change and surprise in hospital settings / Holly J Lanham, Jacqueline A Pugh, David C Aron and Luci K Leykum -- Chapter 14. Simulation to Solve Health System Problems / Mary D Patterson and Ellen S Deutsch -- Chapter 15. Cross-Boundary Teaming to Establish Resilience Among Isolated 'Silos' / Kyota Nakamura, Shin Nakajima, Takeru Abe and Kazue Nakajima -- Chapter 16. "What on Earth Is Going on and What Should I Do Now?" Sensemaking as a qualitative process / Kate Churruca, Louise A Ellis, Janet C Long and Jeffrey Braithwaite -- Chapter 17. Deep Inside the Genomics Revolution: On the frontlines of care -- Stephanie Best, Janet C Long, Elise McPherson, Natalie Taylor and Jeffrey Braithwaite -- Information Classification: General -- Chapter 18. Much More Than Old Wine in New Bottles: Soft Systems Methodology (SSM) for healthcare improvement / Hanna Augustsson, Kate Churruca and Jeffrey Braithwaite -- Chapter 19. Conclusion: On progress, directions and signposts to a transformed healthcare system / Jeffrey Braithwaite and Frances Rapport.
OCLC-licensed vendor bibliographic record.
Keywords: Medical care -- Research -- Methodology; Qualitative research; Health care reform; MEDICAL / Research; MEDICAL / Nursing / Research & Theory